World Bank Group Strategy - World Bank Group (Washington, DC, 2013)
The World Bank Group will focus its financial and technical resources to ending extreme poverty and promoting shared prosperity in a sustainable manner, especially in fragile states, Sub-Saharan Africa, and South Asia. To this end, it is pulling its specialized agencies (IBRD, IDA, IFC, MIGA) to work more closely in all the areas of engagement, from data collection to socio-economic analysis, technical policy advice, lending, investment, risk mitigation, training and knowledge, as well as looking to strengthen partnerships worldwide, especially within the private sector.